Carbon Accounting and Sustainability Reporting: A Systematic Literature Review on Sustainability Accounting Research - Marliani Marliani; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
The rising global climate emergency has placed the shift to net-zero emissions as a foremost strategic concern for companies globally. This research intends to investigate thoroughly the significance of carbon accounting in enhancing the quality of sustainability reporting and its effects on corporate value utilizing a Systematic Literature Review (SLR) method. The evaluation took place through credible literature from the last thirty years, concentrating on the evolution of reporting standards, challenges in sectoral implementation, and the reactions of capital markets to carbon disclosures. The review results indicate that the implementation of carbon accounting aligned with global frameworks, such as the GHG Protocol and IFRS S2, contributes significantly to increased transparency and corporate social legitimacy. However, the study also identifies structural barriers in the form of inconsistencies in emissions measurement methodologies and a disconnect between reporting practices and long-term sustainability goals, particularly in high-emissions sectors such as automotive and energy. Furthermore, the findings suggest that carbon disclosure acts as a value protector in mitigating climate risks, although profitability remains the primary determinant in directly assessing corporate value. The study concludes that digital transformation and the convergence of reporting standards are crucial catalysts in ensuring corporate accountability. The implications of this study emphasize the need for synergy between government regulations and managerial commitment in presenting sustainability reports that are honest, measurable, and based on scientific data for the stability of the green economy in the future.